PREEMPTIVE ANALGESIC EFFECT OF MAGNESIUM SULFATE ON POSTOPERATIVE PAIN IN PATIENTS UNDERGOING LUMBAR FUSION SURGERY - Delavari, Abasali; Lak, Marzieh; Arragizade, Hassan; Salatini, Babak (Faculty of Medicine, Trisakti University, 2019)
BackgroundReducing postoperative pain can improve patient satisfaction and hospital cost. Intravenous magnesium sulfate is one of the proposed drugs for preemptive analgesia. The study aimed to evaluate the effect of magnesium sulfate on postoperative pain in patients undergoing lumbar fusion surgery.MethodsA double-blind randomized clinical trial was conducted on candidates for vertebral fusion surgery with American Society of Anesthesiologists (ASA) class I-II. One hundred and two patients were randomized into the magnesium sulfate group and control group. The magnesium sulfate group received magnesium sulfate at a dose of 50mg/kg in 20 mL volume and infused during 15-30 minutes pre-operation, while the control group received 20 mL normal saline. The severity of the pain was assessed by the Visual Analogue Scale (VAS) at 2, 4, 6, 12 and 24 hours after patients entering the post-anesthetic care unit. After the operation, the patients? relaxation rate was assessed based on Ramsay sedation score (RSS).ResultsThere was no significant difference at 2, 4, 6, 12 and 24 hours post-operation between the two groups in the mean severity of pain (p>0.05). There was no significant difference at 2, 4, 6, 12 and 24 hours post-operation between the two groups in the mean of pethidine consumption. There was no significant difference in the relaxation of the patients according to the RSS criteria in the magnesium sulfate and control groups (p=0.162). ConclusionPre-operative administration of magnesium sulfate does not affect reduction in postoperative pain and opioid consumption of patients undergoing lumbar fusion surgery.